Biotechnological Processes in Microbial Amylase Production. (9th February 2017) - Gopinath, Subash C. B.; Anbu, Periasamy; Arshad, M. K. Md; Lakshmipriya, Thangavel; Voon, Chun Hong; Hashim, Uda; Chinni, Suresh V.
Abstract : Amylase is an important and indispensable enzyme that plays a pivotal role in the field of biotechnology. It is produced mainly from microbial sources and is used in many industries. Industrial sectors with top-down and bottom-up approaches are currently focusing on improving microbial amylase production levels by implementing bioengineering technologies. The further support of energy consumption studies, such as those on thermodynamics, pinch technology, and environment-friendly technologies, has hastened the large-scale production of the enzyme. Herein, the importance of microbial (bacteria and fungi) amylase is discussed along with its production methods from the laboratory to industrial scales.